Enabling Mobile Health. (2017) - Turner, Anthony P.F.
Abstract: The need for new, easy-to-use, home and decentralised diagnostics is now greater than ever and it is rapidly becoming apparent that biosensors can contribute substantially to reducing healthcare costs. New thinking is crucial to finding effective solutions that deliver the high quality of life rightly demanded by our ever ageing population while leveraging technology to deliver this in a cost-effective manner. Several key drivers are catalysing change. Personalised medicine recognises that every individual is different and needs a tailor-made health package; these differences can only be identified with an appropriate suite of diagnostics. Individuals are increasing recognising that data about their bodies should be owned by them and that they should have the choice to use and supplement this information. This generates consumer choice and drives evidence-based payment, where the success of outcomes needs to be measured. Focus on the individual and their needs drives decentralisation and the possible radical restructuring of how we deliver health management. We already see "health rooms" in pharmacies, but the next step will be health rooms in your home, in your pocket or on your wrist. These advances are underpinned by technologies facilitating mobility and data processing, but at the core are rapid, convenient and easy ways to measure our body chemistries at the genomic, proteomic and metabolomic levels. This presentation will focus on meeting these challenges using paper-based electronics, polymers and integrated electrochemical systems to deliver inexpensive instruments for a wide range of bioanalytical applications. Approaches will be illustrated by multi-parametric monitoring for the management of diabetes, chronic kidney disease and stress, reversible and label-free affinity sensors for cancer markers and heart disease, aptasensors for pathogens and cancer cells, and robust microbial-differentiation arrays. Further development will result in cost reduction and a diversity of formats such as point-of-care tests, smart packaging, telemetric strips and print-on-demand analytical devices.